ADAT BOKA: ANALYSIS OF SOCIAL STRATIFICATION FROM THE PERSPECTIVE OF ISLAMIC LAW (CASE STUDY IN SANDI VILLAGE, BUTON WAKATOBI REGENCY) - Mariafu, Mariafu; Sanmas, Abu; Tohe, Ansar (Universitas Islam Negeri Mataram, 2025)
Boka is a form of dowry with a fixed amount determined by the social stratification of women within the customary system. Sandi Village, located in Buton Wakatobi Regency, Southeast Sulawesi Province, is among the communities that still preserve the Boka tradition. This study aims to explore the practice of Boka in marriage ceremonies in Sandi Village and to analyze its compatibility with Islamic law, particularly through the lens of the maslahah (public interest) theory. The main objective is to examine how the Boka tradition is implemented, including the establishment of dowry values based on women's social hierarchy, and to assess whether this tradition aligns with Islamic principles that emphasize social harmony and justice. This research employs a qualitative approach, with fieldwork conducted in Sandi Village, Buton Wakatobi Regency. The analysis is descriptive and qualitative. The findings reveal the dynamic practice of Boka in the community's marriage rituals, showing a significant relationship between the amount of the dowry (Boka) and the traditional social stratification of women (Kaomu, Walaka, Papara). The Boka value is fixed and non-negotiable, intended to maintain women's social status in Butonese society.